Shalat sebagai Inspirasi Kesalehan Sosial (Komparasi Teori Mukasyafah Shalat Ibnu Arabi dan Implikasi Sosial Shalat Harun Nasution) - Alif, Muhtarul; Rijal, Muhammad Azka (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
This research aims to examine aspects of Islam, especially prayer, through a Sufism approach using Ibn Arabi and Harun Nasution's bukasyafah theory. Prayer is the most important act of worship mentioned by the Prophet Muhammad as a pillar of religion. Whoever prays well, then his other deeds are good, and whoever prays badly, then his other deeds are also bad. This statement certainly equates the quality of prayer with other charities, especially social charities. However, often the prayers that a person performs do not have positive implications for a person's social life. The aim of this research is to examine prayer from the perspective of bukasyafah and its relationship to social piety. The method used in this research is content analysis with the main reference being the thoughts of Ibnu Arabi and Harun Nasution. These two figures are manifestations of classical and contemporary Sufism figures. The results of this research are that a person who presents God's majesty in all his actions and words in prayer will be able to absorb God's superiority in all his daily activities. Prayers like this are able to forge a person's morality so that vile and evil actions do not arise in his heart. This prayer is what is able to make a servant always devoted to Allah in all of His creatures so that his presence always has positive value for society.